Candida: an unexpected cause of the acute abdomen. (29th December 2010) - Thrumurthy, Sri Ganeshamurthy; Tiew, Stephenie; Wood, Nicholas; Bhowmick, Arnab
Abstract : The infected intrauterine contraceptive device (IUCD) is a well-described cause of the acute abdomen. However, severe pelvic infection from Candida is an extremely rare complication of the IUCD. We present the first reported description of a Candida-infected IUCD manifesting as an acute abdomen where the degree of infection precluded a conclusive diagnostic workup and necessitated multiple laparotomies. This case highlights the importance for the clinicians to thoroughly exclude such causes of acute sepsis even after exclusion in the presenting history.